Hydrothermal synthesis of ZnO decorated reduced graphene oxide: Understanding the mechanism of photocatalysis. Issue 2 (June 2015) - Kavitha, M.K.; Pillai, Suresh C.; Gopinath, Pramod; John, Honey
Abstract: ZnO nanomaterials are grown in - situ on graphene oxide (GO) materials by a facile hydrothermal method at a temperature of 100 °C. These ZnO–graphene composite materials display a strong and broad absorption in the visible region besides an intense UV absorption peak. The enhanced fluorescent quenching observed for the graphene hybrids compared to ZnO, indicates the photoinduced electron transfer between ZnO and graphene layers, which in-turn reduces the recombination of charge carriers. In order to understand the mechanism of improved photocatalytic properties, reagents such as a radical scavenger t -BuOH and a hole scavenger EDTA-2Na were employed. The addition of t -BuOH did not show any appreciable changes in the photo-degradation properties of the ZnO–graphene hybrids. However, the addition of EDTA-2Na significantly reduced the photocatalytic activities of the ZnO–graphene hybrids indicated that photo-generated holes are the main reactive oxidative species responsible for the photocatalytic reaction. It has been concluded that the excellent absorption range, efficient charge transportation and separation and high surface area make the ZnO–graphene hybrids a better photocatalyst under UV and visible light.